Nuclear and Mitochondrial Gene Data Support Recent Radiation within the Sea Spider Species Complex Pallenopsis patagonica - Dömel, Jana S.; Melzer, Roland R.; Harder, Avril M.; Mahon, Andrew R.; Leese, Florian (Frontiers in Ecology and Evolution, 2017)
The climate history of the Antarctic continental shelf has formed a diverse benthic ecosystem over evolutionary time scales. The extent of faunal diversity has only recently been unveiled especially by using genetic data. In addition to newly reported species, known species of benthic invertebrates in the Southern Ocean turned out to be in fact species complexes representing genetically very distinct clades. Previous studies have shown that the sea spider Pallenopsis patagonica is such a species complex consisting of several mitochondrial clades. However, genetic analyses of another sea spider complex, Colossendeis megalonyx, showed that looking at one gene only can lead to overestimation of species number within a species complex. In this study we expand the current data set of P. patagonica by adding not only samples from Patagonia, the Subantarctic and the Eastern Weddell Sea, but also sequence data of the nuclear internal transcribed spacer region to obtain more information about the species complex. In fact, the number of clades is reduced when looking at nuclear data, but there are no cases of mito-nuclear discordance and hence no evidence for hybridization and speciation reversal events between divergent mitochondrial clades as has been reported for C. megalonyx. As patterns of genetic differences within P. patagonica and C. megalonyx are very similar when looking at the mitochondrial COI gene and also molecular dating of both species complexes suggest a recent separation of clades during the Pleistocene, different biological processes seem to have led to fast and stable species boundaries in P. patagonica as opposed to C. megalonyx where hybridization even across major mitochondrial lineages was still possible.